Biotechnology for Sustainability and Social Well Being - Show, Pau Loke; Ogino, Chiaki; Ibrahim, Mohamad Faizal (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book covers the latest development of bioprocess technology including theoretical, numerical, and experimental approaches in biotechnology as well as green technology that bridge conventional practices and Industry 4.0. Bioprocessing is one of the key factors in several emerging industries of biofuels, used in the production of biogas, bioethanol, and biodiesel; industrial enzymes; waste management through biotechnology; new vaccines; and many more. It is hoped that the novel bioprocess and green biotechnologies presented in this book are useful in assisting the global community in working towards fulfilling the Sustainable Development Goals (SDG) of the United Nations.